2019
DOI: 10.1016/j.atmosenv.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic amines at the Cape Verde Atmospheric Observatory: Abundance, origins and sea-air fluxes

Abstract: Aliphatic amines are important constituents of the marine environment. However, their biogenic origins, formation processes and roles in atmospheric chemistry are still not well understood. Here we present measurements of monomethylamine (MMA), dimethylamine (DMA) and diethylamine (DEA) from two intensive sampling campaigns at the Cape Verde Atmospheric Observatory (CVAO), a remote marine station in the tropical Atlantic Ocean. The amines were measured in the sea surface microlayer (SML), in bulk seawater, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 70 publications
(95 reference statements)
3
29
0
Order By: Relevance
“…1, Tables S2, S5) since no correlation between these parameters and the concentration or enrichment of FAAs was found. This is consistent with other publications which observed that the amino acid concentration in seawater is not related to environmental parameters such as wind, humidity and light (Kuznetsova et al, 2004;van Pinxteren et al, 2012). The results of the individual FAA concentrations in seawater (ULW, SML) and their EF SML , listed in Table S3, show clear differences between the individual amino acids and the amino acid classes.…”
Section: Free Amino Acids In Seawater Samplessupporting
confidence: 91%
See 2 more Smart Citations
“…1, Tables S2, S5) since no correlation between these parameters and the concentration or enrichment of FAAs was found. This is consistent with other publications which observed that the amino acid concentration in seawater is not related to environmental parameters such as wind, humidity and light (Kuznetsova et al, 2004;van Pinxteren et al, 2012). The results of the individual FAA concentrations in seawater (ULW, SML) and their EF SML , listed in Table S3, show clear differences between the individual amino acids and the amino acid classes.…”
Section: Free Amino Acids In Seawater Samplessupporting
confidence: 91%
“…Interestingly, in the second half of the campaign, the FAA concentration was higher than in the first part. Previous studies in different oceanic areas (Kuznetsova and Lee, 2002;Kuznetsova et al, 2004;Reinthaler et al, 2008;van Pinxteren et al, 2012;Engel and Galgani, 2016) have already reported a generally strong variability in FAA concentrations, especially in the SML. Reinthaler et al (2008) concluded that the SML in the open ocean is a highly variable environment with high concentrations of dissolved FAAs and their high enrichment in the SML is without clear diel variations in their concentrations.…”
Section: Free Amino Acids In Seawater Samplesmentioning
confidence: 89%
See 1 more Smart Citation
“…The samples and blank samples were analyzed using the freezing array INDA, which is based on the design ofHill et al (2016) and described in Chen et al (2018) and Hartmann et al (2019). The determination of the ambient N INP in the immersion freezing mode as a function of temperature T is based on Vali (1971). In order to make samples and blank samples comparable, the blank samples were normalized with the same air volume as the corresponding sample, though naturally no air was sucked through the blind samples.…”
Section: Inp Sampling and Measurementmentioning
confidence: 99%
“…High concentrations (4.4 and 7.2 nmol m −3 , respectively) of particulate dimethylamine (DMA) and trimethylamine (TMA), which are probably associated with local biogenic emissions, were observed over the Yellow Sea and the Bohai Sea in May 2012 (Hu et al, 2015). In the North Atlantic, the concentrations of particulate amines were significantly higher during high biological activity periods than during low biological activity periods, and the contributions of amines to secondary organic aerosols and water-soluble organic nitrogen reached 11% and 35%, respectively (Facchini et al, 2008). Van Pinxteren et al (2019 reported that amines in the seawater and gas phase are connected to biological activity of marine and found the transfer of amines was being determined by gas-to-particle conversion rather than via primary processes.…”
Section: Introductionmentioning
confidence: 99%